2022
DOI: 10.3390/ma15103466
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Guided Waves to Improve Damage Detection and Localization in Multilayered CFRP Panel

Abstract: Multilayered carbon fiber-reinforced polymers (CFRP) are increasingly used in aircraft components because of their superior mechanical properties. However, composite materials are vulnerable to impact loads, resulting in delamination-type damage which, if unnoticed, could lead to catastrophic structural failure. The objective of this research was to investigate possibilities to improve damage detection and the localization using signal processing methods. Numerical modeling using the semi-analytical finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Figure 12 shows the Hilbert envelope of the asymmetrical mode of guided wave signals received at various receiver positions. The envelope of the guided wave signal, represented by H(t), is obtained using the Hilbert transform and can be expressed using the following equation [45]: In the case of defect-free, both S 0 and A 0 modes are reflected from the leading and trailing edge of the plate. In the case of delamination, the A 0 mode is reverberated multiple times within the delamination due to the displacement profile of the A 0 mode being perpendicular to the delamination.…”
Section: Localization Of Delamination Using An Analytical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 12 shows the Hilbert envelope of the asymmetrical mode of guided wave signals received at various receiver positions. The envelope of the guided wave signal, represented by H(t), is obtained using the Hilbert transform and can be expressed using the following equation [45]: In the case of defect-free, both S 0 and A 0 modes are reflected from the leading and trailing edge of the plate. In the case of delamination, the A 0 mode is reverberated multiple times within the delamination due to the displacement profile of the A 0 mode being perpendicular to the delamination.…”
Section: Localization Of Delamination Using An Analytical Modelmentioning
confidence: 99%
“…Figure 12 shows the Hilbert envelope of the asymmetrical mode of guided wave signals received at various receiver positions. The envelope of the guided wave signal, represented by H(t), is obtained using the Hilbert transform and can be expressed using the following equation [45]:…”
Section: Localization Of Delamination Using An Analytical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] studied the interaction of ultrasonic guided waves and delamination in a 23-layer Alcoa Advanced Hybrid Structural plate. Papanaboina et.al [6] focused on the numerical analysis of the guided waves propagation in a multilayered CFRP structure to refine damage detection and its localization using different signal processing methods. studied the defect and waviness detection in a layered composite using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that A0 mode dispersion at delamination's in composites is more complex and intricate than in isotropic plates [14], and it is affected by the delamination size to wavelength ratio as well as the delamination damage location through the thickness of the plate. Papanaboina et al [22] investigated multi-layered carbon fibre reinforced panel (CFRP) composites and determined the depth of delamination by comparing the A0 mode's amplitude and estimating location by calculating TOF. Hervin et al [15] employed the A0 mode to explore GW scattering and propagation in a quasi-isotropic laminate with asymmetrically positioned delamination at various depths, and full-field noncontact laser measurements were used to observe wave entrapment and scattering in the delaminated zone.…”
Section: Introductionmentioning
confidence: 99%